First investigation of quartz and calcite shape fabrics in strained shales by means of X-ray tomography. (January 2020) - Saur, H.; Sénéchal, P.; Boiron, T.; Aubourg, C.; Derluyn, H.; Moonen, P.
Abstract: We document the evolution of the 3D fabric of shale along a km-long strain gradient in the Jaca basin (Southern Pyrenees, Spain). With respect to the distance from a thrust, samples were collected in the cleavage-free domain, at the onset of the pencil-cleavage domain, within the pencil-cleavage domain and within the slaty-cleavage domain. By combining high resolution X-ray computed tomography (XCT) and energy dispersive X-ray spectroscopy (EDS), the morphology and the Shape Preferred Orientation (SPO) of thousands of quartz grains, calcite grains and pores was studied. In the least deformed samples, quartz and calcite display mean foliation parallel to bedding with comparable dispersion. In the pencil-cleavage domain, quartz foliation still follows the bedding while calcite foliation is mostly governed by cleavage. In the slaty-cleavage domain, calcite shows a much better organization, with foliation parallel to cleavage, mimicking closely the pore fabric. By contrast, the quartz shape fabric is much less defined, scattered between bedding and cleavage planes. This suggests that quartz grain act as rigid marker in the ductile matrix, while calcite grain orientation is governed by dissolution-precipitation processes. Highlights: Fine-grained rock fabric is investigated by X-ray tomography and SEM-EDS. Samples cover all stages of cleavage development along a strain gradient. Shape preferred orientation of quartz, calcite and pores is studied. Deformation imprints differently on the grain shape fabric of quartz and calcite. Grain fracturing, rotation and pressure-solution identified as dominant processes.